A spectrally bright wavelength-switchable vacuum ultraviolet source driven by quantum coherence in strong-field-ionized molecules - Yuexin Wan; Zhaoxiang Liu; Jinping Yao; Bo Xu; Jinming Chen; Fangbo Zhang; Zhihao Zhang; Lingling Qiao; Ya Cheng (New Journal of Physics, 2021)
We report generation of spectrally bright vacuum ultraviolet (VUV) and deep UV (DUV) coherent radiations at the wavelengths of 192 nm, 198 nm and 204 nm. These DUV/VUV radiations originate from resonant four-wave mixing assisted by quantum coherence in tunnel-ionized CO molecules. The electronic coherence is created when the pump pulses resonantly excite electronic transitions of CO ^+ . The technique allows for the selective switch of DUV/VUV wavelengths provided by the abundant energy levels of molecular ions. The developed source can have arbitrary polarization states by manipulating the polarization of the pump pulse. It also exhibits a spectral bandwidth of 5∼7 cm ^−1 , a divergence angle of 3∼5 mrad, a pulse duration of ∼10 ps, and a photon flux of ∼10 ^10 photons/s. The superior temporal and spectral properties give rise to a broadband Raman comb in the DUV/VUV region.